2022
DOI: 10.1097/ta.0000000000003738
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: Sex bias in pharmacologic venous thromboembolism prophylaxis

Abstract: BACKGROUND:The optimal enoxaparin dosing strategy to achieve venous thromboembolism (VTE) prophylaxis in trauma patients remains unclear.Current dosing guidelines often include weight, age, and renal function but still fail to achieve appropriate prophylactic anti-Xa levels in many patients. We hypothesized that additional patient factors influence anti-Xa response to enoxaparin in trauma patients. METHODS:This is a retrospective review of patients admitted to a Level 1 trauma center for ≥4 days from July 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition to dosing strategy, female gender was associated with higher likelihood of anti‐Xa levels being at or above target in our multiple logistic regression analysis. Previous studies have also found that males were more likely to have subtherapeutic anti‐Xa levels 33,34,40 . Although not extensively studied, a plausible explanation could be related to gender differences in body composition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to dosing strategy, female gender was associated with higher likelihood of anti‐Xa levels being at or above target in our multiple logistic regression analysis. Previous studies have also found that males were more likely to have subtherapeutic anti‐Xa levels 33,34,40 . Although not extensively studied, a plausible explanation could be related to gender differences in body composition.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have also found that males were more likely to have subtherapeutic anti-Xa levels. 33,34,40 Although not extensively studied, a plausible explanation could be related to gender differences in body composition. Lean muscle tends to be more highly vascularized compared to adipose tissue, so taller muscular patients on average would be expected to have higher blood volume and larger enoxaparin volume of distribution than shorter patients with the same weight.…”
Section: Discussionmentioning
confidence: 99%